Uncertainty and possibility new approaches to future making in design anthropology - Akama, Yoko; Pink, Sarah 1966-; Sumartojo, Shanti 1970- (Bloomsbury Academic, 2018)
"Uncertainty is increasingly central to scholarship, research and practice across design, social science and humanities disciplines. Both theoretical concepts and empirical investigations of uncertainty and possibility are emerging as scholars and practitioners seek news ways to understand and intervene in a world of crisis with creativity, hope and speculation. This ground-breaking book offers new perspectives on the central issues of uncertainty and possibility and identifies new research methods which take advantage of disruptive and experimental techniques. Advancing a practical agenda for future making, it reveals how uncertainty can be engaged as a generative 'technology' for understanding, researching and intervening in the world. Drawing on key themes in creative methodologies - making, essaying, inhabiting, gathering - the eight chapters explore contemporary sites of practice, such as maker spaces and technology design, the imaginaries of architectural design, the temporalities of built cultural heritage, and interdisciplinary making and performing. Based on the authors' own academic work and their applied research with a range of different organizations, Uncertainty and Possibility outlines new opportunities for research and intervention. Supported by online resources, it is essential reading for students, scholars and practitioners in design anthropology and design."...
Hier auch später erschienene, unveränderte Nachdrucke. Includes bibliographical references and index
Keywords: Design -- Anthropological aspects; Maker movement; Architectural design; Uncertainty; Design; Ungewissheit; Anthropologie; Sachkultur; Ethnologie; Kunst; Architektur; Aufsatzsammlung